INTERACTIVE MEDIA APPLICATION FOR TOURIST ATTRACTIONS IN THE CITY OF BANDUNG - Rijayana, Iwan; , Surgani; Fahruroji, Ramdan; Suwardi, Muhammad Yusuf; Aprijal, Andri Rizki; Gunawan, Indra (CENTRAL ASIA AND THE CAUCASUS, 2022)
Bandung is a city located in the West Java Province of Indonesia, which is famous for its natural beauty and has many entertainments, culinary and other shopping places. At the weekend many tourists come to Bandung, This is because in Bandung there are many tourist places which very interesting, but tourists do not know more about its location well. Tourists who come to the city of Bandung cannot enjoy all the tourist attractions because they lack information about the existence of tourist attractions. That's why they need a media which can help tourists who visited Bandung to easily find location information and provide a map media so tourists can find the way to place that they want to visit.The purpose of this study is to help tourists who come to visit the city of Bandung in finding information on roads and tourist destinations so that it is expected to increase foreign exchange for the local government of Bandung.The result of the research is To develop this application using Macromedia Flash with Action Script. This application has been successfully implemented to PDAs. With the implementation of this application into PDA so the tourist has an information resource that is practical and easy to bring it anywhere. With building an interactive media application that has facilities to browse the map, select place, view info, and view photo. Hope this can reduce the problems above. This application is interactive media based on Macromedia Flash which was implemented to PDA.